Comparison of Streptococcus mutans Adhesion with Different Concentrations in Artificial Saliva to Fixed Orthodontic Materials in Laboratory Conditions - Leila Mohammadpour Belvirdy; Ahmad Sheibaninia; Shadab Safarzadeh Khosroshahi; Seyyed Khalil Shokouhi Mostafavi; Mohammad Javad Kharazi Fard (Biomedical and Biotechnology Research Journal)
Background: Biofilm accumulation is a common complication of orthodontic treatment, occurring in approximately 60% of patients. The irregular surfaces of orthodontic appliances (archwires, brackets, and braces) create retention areas that hinder effective oral hygiene, increase bacterial load, and alter oral microbiota, potentially leading to pathogenic species proliferation. In addition, factors such as buffering capacity, pH levels, and saliva flow are crucial for optimal oral function and caries prevention. This study aimed to compare the adhesion of Streptococcus mutans at different concentrations in artificial saliva to fixed orthodontic materials under laboratory conditions. Methods: S. mutans strains were obtained from the National Center for Genetic and Biological Resources in Tehran, along with normal artificial saliva prepared with pH values of 5 and 7. Bacterial adhesion was quantified by counting colony-forming units on culture media. The effects of bracket type, archwire material, composite type, and saliva pH on bacterial adhesion were analyzed using Generalized Estimating Equations with a significance level of 0.05, employing SPSS software (version 26). Results: A significant difference in adhesion rates of S. mutans was observed between different archwire types at both pH levels (P = 0.001). However, no significant differences were found in adhesion rates among the three bracket types (plastic, metal, and ceramic) or between self-cure and light-cure composites at both pH levels. Overall, the study indicated a significant interaction effect among archwire type, bracket type, and composite type on bacterial adhesion. Conclusion: The adhesion of S. mutans to orthodontic materials in laboratory conditions is influenced by archwire type but not by bracket type or composite type. These findings underscore the importance of selecting appropriate orthodontic materials to mitigate bacterial adhesion and improve oral health outcomes during treatment.